MEMÓRIA E FETICHIZAÇÃO DA MERCADORIA - Tfouni, Fabio Elias Verdiani (Organon, 2003)
The questions we address here are: What is the relation betweenmemory and forgetfulness? What is the relation between a discursivememory and the fetishism of merchandise? We argue that this fetishismcan be seen in the discursive memory. However, something remainsimpossible to remember: the memory of the merchandise-form, which isthe merchandise’s production relation chain. We study these issues on twoslogans.